Effect of cold rolling on tensile properties and microstructure of high nitrogen alloyed austenitic steel. (February 2014) - Sun, S. C.; Mu, J. W.; Jiang, Z. H.; Ji, C. T.; Lian, J. S.; Jiang, Q.
<x content-type="archive" xml:space="preserve">Abstract</x> The cold rolling strain effect on the tensile properties of a high nitrogen alloyed austenitic steel was systemically investigated. Quasi-static tensile experiments were performed on the samples with different cold rolling strain. The material possessed good balance between strength and ductility in the entire rolling strain range. Mechanical property and microstructure of the nitrogen alloyed austenitic steel were greatly affected by cold rolling strain. With the increase in cold rolling strain, the strength increased sharply but the ductility declined. That is related to the gradual changes of microstructure induced by the cold rolling process. The cold rolling process leads to substantial microstructural change, from the appearance of slip bands and twins at low cold rolling strain; the microtwins formation at intermediate cold rolling strain and followed by sequences of their bending, breaking and disappearance; and finally to the formation of drossy twins at the high cold rolling strain.